Research on r_n Remainder Array New Algorithm of Narrow or Widen by Needles on Woolen Sweater CAD - Liu, Yao; Deng, Zhong-min (Procedia environmental sciences, 2011)
For the deficiencies of narrow or widen algorithms on woolen sweater CAD, this paper puts forward a new algorithm named r_n remainder array algorithm base on the traditional algorithms by the analysis of the rules of it. It is divided into non-remainder segment and the remainder segment. Visual C++ will be used to control and simulation the curve of woolen sweater garment piece. r_n remainder array algorithm has the character of the simple expression, convenient computing and good simulation results.